The implementation of sustainable and innovative architecture solutions to the reconstruction of the hangar project - Mickaitis, Marius; Lakštauskienė, Violeta (Journal of Architecture and Urbanism, 2013)
Creating group work places is an important topic to be resolved in order to improve educational infrastructure and use modern methods of learning. One of the possible solutions to consider this situation could be the reconstruction of an abandoned hangar or other comparable building. The principles of sustainable architecture should be applied for planning and implementing reconstruction solutions. Different internationally and nationally functioning systems for certifying sustainable building have accumulated wide experience and have perfected the proposed schemes. The optimization of the established criteria required for a specific type of an object enables to achieve balanced and sustainable innovative architectural solutions to new constructions or renovations. The paper is aimed at evaluating the possibilities of applying innovative principles of sustainable architecture reconstructing the hangar to make it an informal educational building or a structure of a similar purpose.Article in Lithuanian.Angaro rekonstrukcija įgyvendinant inovatyvius darnios architektūros sprendimusSantrauka. Siekiant pagerinti studijų infrastruktūrą ir pritaikyti šiuolaikinius mokymosi metodus, grupinio darbo vietų sukūrimas dažnai tampa aktuali problema. Vienas iš galimų jos sprendimo būdų yra rekonstruoti apleistą angarą ar kitą panašų statinį. Planuojant ir įgyvendinant rekonstrukcijos sprendimus, taikytini aktualūs darnios ir tvarios architektūros principai. Taikant tarptautiniu ir nacionaliniu lygiu veikiančias skirtingas darnias pastatų sertifikavimo sistemas sukaupta nemažai patirties ir ištobulintos siūlomos schemos. Jų reikalavimų kriterijų optimizavimas konkrečiam objekto tipui leistų pasiekti subalansuotus ir inovatyvius darnios architektūros sprendimus naujos statybos arba renovacijos atvejais. Šio darbo tikslas yra įvertinti inovatyvių darnios ir tvarios architektūros principų taikymo galimybes rekonstruojant angarą į neformalų studijų ar panašios paskirties pastatą.Reikšminiai žodžiai: darni architektūra, inovatyvūs sprendimai, angaro rekonstrukcija, pastatų renovacija.